La elección del auxiliar en italiano - Romani, Patrizia (Cuadernos de Filología Italiana, 2010)
The article deals with the selection of the auxiliary essere (‘to be’) or avere (‘to have’) in the formation of compound tenses of Italian, and it explains it according to the argumental and thematic structure of the predicate. Italian verbs can be divided into two large groups: those which assign a Θ-role to the deep subject, such as transitive and inergative verbs, and those which do not assign it, such as inaccusative, pronominal, passive, meteorological and rising verbs; the former select avere and the latter choose essere. Auxiliary selection has a diathetic meaning in Italian, because it expresses what kind of relation exists between grammatical subject and the event denoted by the predicate. Auxiliary selection conveys systematically the opposition between “active” and “nonactive” voice.